Safety and efficacy of (+)‐epicatechin in subjects with Friedreich's ataxia: A phase II, open‐label, prospective study. Issue 2 (31st August 2020) - Qureshi, Muhammad Yasir; Patterson, Marc C.; Clark, Vicki; Johnson, Jonathan N.; Moutvic, Margaret A.; Driscoll, Sherilyn W.; Kemppainen, Jennifer L.; Huston, John; Anderson, Jeff R.; Badley, Andrew D.; Tebben, Peter J.; Wackel, Philip; et al.
Abstract: Background: (+)‐Epicatechin (EPI) induces mitochondrial biogenesis and antioxidant metabolism in muscle fibers and neurons. We aimed to evaluate safety and efficacy of (+)‐EPI in pediatric subjects with Friedreich's ataxia (FRDA). Methods: This was a phase II, open‐label, baseline‐controlled single‐center trial including 10 participants ages 10 to 22 with confirmed FA diagnosis. (+)‐EPI was administered orally at 75 mg/d for 24 weeks, with escalation to 150 mg/d at 12 weeks for subjects not showing improvement of neuromuscular, neurological or cardiac endpoints. Neurological endpoints were change from baseline in Friedreich's Ataxia Rating Scale (FARS) and 8‐m timed walk. Cardiac endpoints were changes from baseline in left ventricular (LV) structure and function by cardiac magnetic resonance imaging (MRI) and echocardiogram, changes in cardiac electrophysiology, and changes in biomarkers for heart failure and hypertrophy. Results: Mean FARS/modified (m)FARS scores showed nonstatistically significant improvement by both group and individual analysis. FARS/mFARS scores improved in 5/9 subjects (56%), 8‐m walk in 3/9 (33%), 9‐peg hole test in 6/10 (60%). LV mass index by cardiac MRI was significantly reduced at 12 weeks ( P = .045), and was improved in 7/10 (70%) subjects at 24 weeks. Mean LV ejection fraction was increased at 24 weeks ( P = .008) compared to baseline. Mean maximal septal thickness by echocardiography was increased at 24 weeks ( P = .031). There were no serious adverse events. Conclusion: (+)‐EPI was well tolerated over 24 weeks at up to 150 mg/d. Improvement was observed in cardiac structure and function in subset of subjects with FRDA without statistically significant improvement in primary neurological outcomes. Synopsis: A (+)‐epicatechin showed improvement of cardiac function, nonsignificant reduction of FARS/mFARS scores, and sustained significant upregulation of muscle‐regeneration biomarker follistatin. Abstract :